Firing the Regional Can(n)on: Liberal Pluralism, Social Agency, and David Adams Richards’s Miramichi Trilogy - Armstrong, Christopher; Wyile, Herb (Studies in Canadian Literature, 1997)
David Adams Richards’s Miramichi trilogy (Nights Below Station Street, Evening Snow Will Bring Such Peace, and For Those Who Hunt the Wounded Down) resists certain forms of critical reception and ideological appropriation. It presents an opportunity to rethink the assumptions, biases, and missions of liberal pluralism and to reflect on the political effects of canon revision. This essay seeks to reassess both the assumptions of the framework in which Janice Kulyk Keefer, in Under Eastern Eyes (1987), slots Richards’s work, and the ways in which his Miramichi trilogy diverges from - and stages resistance to - his critical reception and cononization, raising not just questions of region and cononicity but also of literacy and class.